Phytochemical screening and antibacterial activity of Acorus calamus Linn. rhizomes - Ali, Saima; Singhal, Madhuri; Ahmed, Mansoor; Wani, Sajad H (Journal of Postharvest Technology, 2024)
Acorus calamus Linn., a member of the Acoraceae family, is often known as the Vacha (Sanskrit)  and Sweet Flag (English). Acorus calamus rhizomes contain potential medicinal properties. The  present study investigated the phytochemical screening and bioevaluation of crude extract as well  as isolated and characterized molecules isolated from Acorus calamus rhizomes. Preliminary  phytochemical study revealed that the extracts are rich in Alkaloids, Flavonoids, isoflavonoids,  carbohydrates etc. The compound α asarone were isolated and characterized from the methanolic  crude extract by using different physiochemical properties. The crude extracts as well as isolated  and characterized molecule were evaluated at different concentrations against different bacteria  (gam positive and gram negative)by using agar well diffusion method. Antioxidant potential of the  crude extract and the pure molecule were evaluated by using standard tests. From this study, it  was found that the extract as well as the pure molecule are potent in limiting the growth of different  bacteria. The most potent were methanolic extract followed by ethyl acetate and ethanol. Thus, the  anti-bacterial/ antioxidant properties of the crude extract and the pure compound(s) as reported in  his work suggest a promising role of these compound(s), which needs to be precisely evaluated so  as to increase their scope in drug discovery research.
Keywords: Acorus calamus; Secondary metabolites; NMR; DPPH; α-Asarone